“The Influence of Descipline, Compensation and Competencies towards Employee Performance (Study at PT Petrokimia Gresik)” - Dwikidyatama Iswara (Jurnal Ilmiah Mahasiswa FEB, 2017)
The competition of agriculture industry especially fertilizer is very tight considering the existence of AEC policy since 2016. This makes local fertilizer company in Indonesia is demanded to improve the quality of its human resources. A good quality of human resources can be measured by good employee performance. This research aimed to investigate factors affecting employee’s performance  especially in fertilizer industry. This study was conducted to determine the effect of discipline, compensation, and competence on employee’s  performance. In this study, PT Petrokimia Gresik serve as an object representing all state-owned fertilizer companies in Indonesia. Population in this research are all permanent employees in PT Petrokimia Gresik whic are 3,173 employees. For sampling technique, this study used Slovin formula calculation with 10% error rate. The samples obtained in this study were 112 employees of PT Petrokimia Gresik. This study was conducted by regression analysis. The results of research show that discipline, compensation, and competence have a significant effect partially on employee’s performance, and competence has a dominant effect on employee’s performance.Keywords: Discipline, Compensation, Competencies, Employee Performance.